2021
DOI: 10.1371/journal.pone.0247032
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterization of turnip greens (Brassica rapa ssp. rapa): A systematic review

Abstract: Objective The Turnip (Brassica rapa L. ssp. rapa) is a leaf and root vegetable grown and consumed worldwide. The consumption of Turnip has been associated with beneficial effects on human health due to their phytochemicals that may control a variety of physiological functions, including antioxidant activity, enzyme regulation, and apoptotic control and the cell cycle. The current systematic review of the literature aims to evaluate both the profile and quantity of phytochemicals commonly found in Turnip greens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…In addition, it is used for lung protection and nephroprotection in Unani and Arab traditional medicine. 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is used for lung protection and nephroprotection in Unani and Arab traditional medicine. 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hydroxycinnamoyl glycosides were highly abundant in rapid cycling and yellow sarson, as well as in Chinese cabbage and komastuna, but low in caixin, broccoletto, and wild cabbage. According to previous reports (Soengas et al, 2018;Dejanovic et al, 2021), sinapic acid derivatives were the major hydroxycinnamic acid derivatives in B. rapa, including 1,2-disinapoyl gentiobiose (compound 147-149) and 1-sinapoyl-2-feruloyl gentiobiose (compound 124-128). These were reported to exhibit antioxidant and anti-inflammatory effects in human plasma and human peripheral blood mononuclear cells (Olszewska et al, 2020).…”
Section: Hydroxycinnamic Acid Derivativesmentioning
confidence: 81%
“…Similarly, quercetin 3-O-triglucoside-7-O-sinapoylglucoside (compound 258) and quercetin 3-O-triglucoside-7-Oferuloylglucoside (compound 257) displayed 5,577-and 3,549fold change among all genotypes, respectively. Previous studies have shown that kaempferol derivatives were the most abundant flavonols in Chinese cabbage, pak choi, turnip, and mizuna (Soengas et al, 2018;Dejanovic et al, 2021;Kyriacou et al, 2021;Wiesner-Reinhold et al, 2021)…”
Section: Flavonolsmentioning
confidence: 99%
“…By promoting a modest portion of diet in the form of vegetables, oil‐rich seed, silage, and organic fertilizer. B. rapa extract contains a variety of volatiles, including terpenoids, ketonic, aldehydes, and esters compounds (Dejanovic et al, 2021). Indole derivatives, phenylpropanoids, aldehydes, lignan, sulfurous compounds, and carbohydrate derivatives have also been discovered in turnip leaves and roots extracts (Paul et al, 2019; Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%